Answer:
x = -6 and x= -1
Explanation:
the expression we have is:
![x+4=√(x+10)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ruhthbzm93w3w1iczpjrmyx6gq5crqqidb.png)
Taking tha square of the whole equation:
![(x+4)^2=x+10](https://img.qammunity.org/2019/formulas/mathematics/middle-school/p4rul6xmt8cbulmtcen0m2llvh92hffpto.png)
solving the binomial squared on the left side with the rule:
![(a+b)^2=a^2+2ab+b^2](https://img.qammunity.org/2019/formulas/mathematics/high-school/3vx0x8variyxdfk6g55loqzegwsn3d84ai.png)
we get:
![x^2+8x+16=x+10](https://img.qammunity.org/2019/formulas/mathematics/middle-school/nxc32kwltat6nif9gmpnljjd6j3sdpa6j4.png)
rearranging all terms to the left:
![x^2+8x-x+16-10=0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/mc36nlf8k090eru6cyrexvbkhkwi074oqx.png)
joining like terms:
![x^2+7x+6=0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/7ctgcvuep1rosivi1mu8s54dkdrx6xh1w5.png)
we can sove this quadratic equation with the quadratic formula, or by factoring:
![x^2+7x+6=(x+6)(x+1)=0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/73imk0xuc32g9vit2z3qq3pydzvid1idzb.png)
and from this we find our two solutions using the zero product property (if a product of thing is equal to zero, one of them must be zero)
![x+6=0\\x=-6](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ilv00dvgm21tesmsfpa38ghcpcmji7sytr.png)
and
![x+1=0\\x=-1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/yijxyswmfbwc67z7umfnggbqyfbmktlx0r.png)